2017
DOI: 10.1080/00016489.2017.1373850
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant diseases and their effect on disease prognosis in Meniere’s disease: diabetes mellitus identified as a negative prognostic factor

Abstract: A patient's concomitant diseases, especially diabetes, should be treated effectively because they might affect the progression of MD. Further studies on the effects of concomitant diseases on MD prognosis are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…The relationship between metabolic disorder and MD has also been suggested. Previous studies have reported that DM is associated with severe hearing loss and frequent vertigo in cases of MD 9 and higher BMI and systolic BP are related to MD 10 . Therefore, the present study results are not consistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The relationship between metabolic disorder and MD has also been suggested. Previous studies have reported that DM is associated with severe hearing loss and frequent vertigo in cases of MD 9 and higher BMI and systolic BP are related to MD 10 . Therefore, the present study results are not consistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…MD is a complex heterogeneous disorder, with multiple factors reported to contribute to its development, 4 including age (older than 60 years), sex (female) 2 , 3 , genetics 5 , 6 , race (white people) 7 , stature and leg length (short) 8 , metabolic disorder 9 , 10 , autoimmunity 10 17 , anatomy 18 , allergies 19 , migraines 20 , weather (high humidity and low atmospheric pressure) 21 , diets, and stress 22 . However, the majority of studies are limited by a lack of population-based cohorts and low number of cases; therefore, the underlying disease pathological pathways remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from 1998 to 2012, the prevalence of asthma, atopic dermatitis, and allergic rhinitis in the Korean adult population also increased from 1.2 to 3.1%, from 1.2 to 17.9%, and from 2.7 to 3.8%, respectively [Yoo et al, 2015;Kang et al, 2018]. These allergic diseases and diabetes have been demonstrated to be more frequent in patients with MD than in the general population [Derebery and Berliner, 2000;Tyrrell et al, 2014;Pieskä et al, 2018]. Further studies of the relationship between dietary and lifestyle changes and MD symptoms and its mechanisms would be needed to manage the symptoms of MD and control the incidence in Asian countries.…”
Section: Discussionmentioning
confidence: 96%
“…All domains of the Cochrane Risk of Bias tool for RCTs will be considered, including selection bias (sequence generation and allocation sequence concealment), performance bias (blinding of participants and personnel), detection bias (blinding of outcome assessment), attrition bias (incomplete outcome data), reporting bias (selective reporting), and other biases considered relevant to the review topic. We will also evaluate baseline imbalances between groups with respect to comorbidities and factors that may impact our outcomes of interest, including history of falls more than once in the past year, older age, white race, female sex, higher BMI, current tinnitus, prior therapies received, allergies, immune dysfunction (e.g., ankylosing spondylitis, systemic lupus erythematosus, psoriasis), autonomic dysfunction, poor mental health [18, 20, 22], arthritis [23], history of hearing loss or episodic vertigo [24], familial history of MD, and diabetes mellitus [25].…”
Section: Methodsmentioning
confidence: 99%